Peningkatkan Karakter Religius Siswa Melalui Internaliasi Nilai dalam Kegiatan Keagamaan dan Sosial - Amin, Moh Nasrul; Nashihin, Muhammad; Nursikin, Mukh (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2024)
This study aims to determine the strategy of internalizing religious character values ​​in religious and social activities and what religious values ​​are internalized in Madrasah Aliyah (MA) Tarbiyatut Tholabah. The approach used is a qualitative approach with a case study design, data collection through interviews, documentation, and observation with informant sources from school leaders, teachers, and students. Data validity using triangulation techniques and data analysis through data reduction, data presentation and verification or data conclusions. The findings show that the strategy of internalizing religious values ​​based on religious and social activities is carried out through first routine activities, namely congregational prayer, routine Koran reading, and activities to commemorate Islamic holidays, second Social Community Activities such as social service programs and community service, third Habitual Approach in Daily Life contained in Islamic culture and daily monitoring by teachers, fourth is the Al-Qur'an Tahfidz Program. The religious values ​​that are internalized are the values ​​of faith and obedience to worship, honesty, responsibility, simplicity, tolerance, social concern. These results highlight the potential of integrating religious and social activities in the curriculum to develop broad-minded individuals who are spiritually grounded and socially responsible. This study contributes to the existing literature by providing empirical evidence on the effectiveness of integrating religious and social activities in character education in Islamic schools that can be recommended for wider implementation in other Islamic educational institutions.